Ghosts of organizations past communities of organizations as settings for change - Ryan, Daniel J. 1956- (Temple University Press, 2015)
In Ghosts of Organizations Past, Dan Ryan asks, "Why are urban communities such hard places to implement community improvement programs?" Looking at New Haven, Connecticut, and a now-defunct program called Fighting Back, which was created to build community coalitions against the abuse of alcohol and other drugs, Ryan shows how the normal properties of organizations generate apparent pathologies. He shows how the "ghosts," or artifacts, of past organizations, both inhibited and enhanced Fighting Back's chances of success. Ryan draws on concepts from the study of organizations, social capital, and social networks to re-think questions such as "What kind of thing is a community?" and "Why is it so difficult to build community initiatives out of organizations?" He provides a social organizational explanation for problems familiar to anyone who has been involved in community programs, issues that are usually understood as personal incompetence, turf wars, greed, or corruption. Ghosts of Organizations Past describes the challenges of using organizations to create change in places in dire need of it.